UTTERANCE AND EXPRESSION SPOKEN BY MOBILE LEGENDS PLAYER - Tri Setianingsih; Baiq Sumarni (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The use of utterances and expressions in mobile Legends games is very often used by students when playing mobile Legends games. Many students used utterances and expressions to show what they are feeling while playing mobile Legends games. This study aimed to find out what types of utterances and expressions students use when playing mobile Legends games with qualitative method. The subjects of this study were students of SMKN 1 Batulayar with a total of 5 students. When playing Legends mobile game. Data in the form of field notes and interview transcripts, based on interviews from students that students use utterances and expressions to show what they feel when playing. The utterances used are constative utterances and performative utterances, as well as using the maxims of quality and maxims of manner while in expressions students use expressions of happy, sad, angry, afraid and surprised therefore in playing mobile Legends games students unconsciously use two types of utterances namely performative and constant utterances as well as maxims of quality and Maxim of manner and use expressions of happy, sad, angry, afraid and surprised in order to show what students feel when playing mobile Legend games. Keywords: Mobile Legend, Utterance, Expression